High-Purity Amino-Functionalized Graphene Quantum Dots Derived from Graphene Hydrogel - Lim,YT; Kim,T; Kulkarni,A; Kim,D (Nano, 2016)
© 2016 World Scientific Publishing Company. The unique properties of graphene quantum dots (GQDs) make them interesting candidate materials for innovative applications. Herein, we report a facile method to synthesize amino-functionalized graphene quantum dots (AF-GQDs) by a hydrothermal reaction. Graphene oxide (GO) was synthesized by Hummer's method where ultra-small GO sheets were obtained by a prolonged oxidation process followed by sonication using an ultrasonic probe. Subsequently, graphene hydrogel (GH) was also obtained by a hydrothermal synthesis method. Proper care was taken during synthesis to avoid contamination from water soluble impurities, which are present in the precursor, GO solution. Following the treatment of GH in ammonia, ultra-small amino-functionalized graphene fragments (AF-GQDs) were formed, which detached from the GH to eventually disperse evenly in the water without agglomerating. This modified synthesis process enables the formation of high-purity AF-GQDs (99.14%) while avoiding time-consuming synthesis procedures. Our finding shows that AF-GQDs with sizes less than 5nm were well dispersed. A strong photoluminescence (PL) emission at ∼410nm with 10% PL quantum yield was also observed. These AF-GQDs can be used in many bio applications in view of their low cytotoxicity and strong fluorescence that can be applied to cell imaging.